Effects of Obesity and Hypertension on Pulse Wave Velocity in Children. Issue 3 (11th August 2016) - Kulsum‐Mecci, Nazia; Goss, Charles; Kozel, Beth A.; Garbutt, Jane M.; Schechtman, Kenneth B.; Dharnidharka, Vikas R.
Abstract : Pulse wave velocity (PWV) is a biomarker of arterial stiffness. Findings from prior studies are conflicting regarding the impact of obesity on PWV in children. The authors measured carotid‐femoral PWV in 159 children aged 4 to 18 years, of whom 95 were healthy, 25 were obese, 15 had hypertension (HTN), and 24 were both obese and hypertensive. Mean PWV increased with age but did not differ by race or sex. In adjusted analyses in children 10 years and older (n=102), PWV was significantly higher in children with hypertension (PWV±standard deviation, 4.9±0.7 m/s), obesity (5.0±0.9 m/s), and combined obesity‐hypertension (5.2±0.6 m/s) vs healthy children (4.3±0.7 m/s) (each group, P <.001 vs control). In our study, obesity and HTN both significantly and independently increased PWV, while African American children did not have a higher PWV than Caucasian children.